Economic Impact of Thermal Insulation of the Building’s Envelope - Al-Juboori, Salloom A. (European Scientific Journal, ESJ, 2018)
Climate change was the beginning of the depletion of fossil fuels, and increasing expansion in investment projects in various sectors of our life, all play a key role in the increasing demand for energy. So energy is considered one of the biggest priorities and challenges facing the world economy due to the lack of conventional energy sources of crude oil and natural gas used in energy generation. The use of thermal insulation materials in building’s envelope is one of the ways to reduce energy consumption. Therefore, this study will address the importance of the use of thermal insulation materials in building’ envelope to reduce energy loss as a result of heating and cooling conditions. The case sudy was the implementation of thermal insulation on Engineering Faculty building’s envelope/ Muta’h University. The thermal loads were calculated for the building, with and without thermal insulation, by using four common different insulation materials which are; Rockwool, foam concert, double-glazing and extended Polystyrene. The selection of these materials depends on availability in the market, cost of implementation and the coefficient of thermal conductivity. The results showed that the polystyrene extended of thickness 10 cm is the best material for the thermal insulation in comparison of the others. The reduction ratio in thermal transmittance reached up to 76%; while in volume ratio of central heating fuel consumption reached up to 26.7%.